Valorization of carbon fiber waste from the aeronautics sector: an application in Li-ion batteries. Issue 6 (12th March 2021) - Savignac, Laurence; Danis, Andrew S.; Charbonneau, Mathieu; Schougaard, Steen B.
Abstract : Recycled carbon fibers coming from the aerospace industry are integrated as the backbone of a high energy density free-standing electrode. Abstract : Carbon fibers developed by the aerospace industry for enhancing the structural integrity of aircrafts represent a hurdle to recycling at the end of the aircraft's service life. A major issue is the short length and entanglement of the fibers, which limits manufacturing processes as well as reemployment targets in other structural composites. A best-case green solution to this growing problem would involve integrating these recycled carbon fibers into an alternative high-value product. Herein, we present novel free-standing electrodes (FSEs) for use in Li-ion batteries that were synthesized from these recycled aerospace carbon fibers. The high mechanical strength fibers were combined with a LiFePO4 active material, selected for its ultrafast charge/discharge capacity, stability, and minimal environmental impact. The recycled carbon fiber content was varied from 0 to 5 wt% to examine its effect on the positive electrode's electrochemical performance and mechanical stability. The resulting LiFePO4 based FSEs exhibited a total electrode capacity of 141 mA h g −1 and an energy density of 468 W h kg −1 . The increase in energy density partly results from the carbon fibers enabling the elimination of the metallic current collector from the composite electrode design. This approach is not environmentally sound for virgin fibers due to the large energy investment required for their production. However, recycled fibers where the energy investment has already been recovered in their primary role offers a unique avenue to enhance Li-ion battery performance, while eliminating an important waste problem.